Endovascular treatment of abdominal aortic aneurysms - Buck, Dominique B. (2013)
Patients with abdominal aortic aneurysms (AAAs) are usually treated with endovascular aneurysm repair (EVAR), which has become the standard of care in many hospitals for patients with suitable anatomy. Clinical evidence indicates that EVAR is associated with superior perioperative outcomes and similar long-term survival compared with open repair. Since the randomized, controlled trials that provided this evidence were conducted, however, the stent graft technology for infrarenal AAA has been further developed. Improvements include profile downsizing, optimization of sealing and fixation, and the use of low porosity fabrics. In addition, imaging techniques have improved, enabling better preoperative planning, stent graft placement, and postoperative surveillance. Also in the past few years, fenestrated and branched stent grafts have increasingly been used to manage anatomically challenging aneurysms, and experiments with off-label use of stent grafts have been performed to treat patients deemed unfit or unsuitable for other treatment strategies. Overall, the indications for endovascular management of AAA are expanding to include increasingly complex and anatomically challenging aneurysms. Ongoing studies and optimization of imaging, in addition to technological refinement of stent grafts, will hopefully continue to broaden the utilization of EVAR.